The Effect of Limb Explosive Power and Wrist Flexion on The Lay-up Shoot Ability of Extracurricular Basketball - Sagiyonar, Ervian Agus; Manullang, Jujur Gunawan; Imansyah, Farizal (Journal of Social Work and Science Education, 2023)
The purpose of this study was to analyze the effect of limb explosive power and wrist flexion on the lay-up shoot ability of extracurricular basketball students of SMA Negeri 4 OKU. This research is a type of Ex Post Facto research that uses a path analysis research design. The population is all basketball extracurricular students of SMA Negeri 4 OKU with a sample of 30 students. The sampling technique is a saturated sample or total population. The data analysis techniques used are quantitative descriptive analysis, requirements tests, and path analysis through the SPSS 20.00 program at a significant level of 95% or α 0.05. The results showed that; (1) There is a direct effect of limb explosive power on wrist flexion in extracurricular basketball students of SMA Negeri 4 OKU with a beta value of 0.603 with a significant level of 0.000 < α0.05; (2) There is a direct influence of limb explosive power on the ability to lay-up the shoot in extracurricular basketball students of SMA Negeri 4 OKU with a beta value of 0.380 with a significant level of 0.002<α0.05 (4) There is a direct effect of wrist flexion on the ability to lay-up the shoot in extracurricular basketball students of SMA Negeri 4 OKU with a beta value of 0.337 with a significant level of 0.004 <α0,05; (6) There is no effect of limb explosive power through wrist flexion on lay-up shoot ability in extracurricular basketball students of SMA Negeri 4 OKU with a beta value of 0.203 (0.203 < 0.380).